Razširjenost in invazivnost robinije (Robinia pseudoacacia L.) v severovzhodni Sloveniji - Rudolf, Sebastian (Gozdarski vestnik, 2006)
The objective of this research was to study the distribution, share, and influence of black locust (Robinia pseudoacacia L.) on the forest stands in northeast Slovenia. The analyses of data from the Slovenian forest service database showed that in the forest management region of Murska Sobota, the growing stock of back locust is highest by the Mura river and on the extensiveMura plain. An inventory of regeneration from 10 sampling locations on 30 small plots revealed aggressive regeneration of black locust in all three analysed management classes, but regeneration was most adundant in the oak-hornbeam forests, which are sometimes converted into pure black locust stands.
Keywords: Robinija pseudoacacia L.; robinija; drevesne vrste; prevalence; razširjenost; severovzhodna Slovenija